An Initial 5-Year Single-Center Experience of 365 Patients Undergoing the Video-Assisted Thoracoscopic Surgery for Nuss Procedure for Pectus Excavatum in Resource-Scare Setting - Nguyen, The-May; Le, Van-Thieu; Nguyen, Huu-Uoc; Pham, Huu-Lu; Phung, Hong-Son Duy; Vu, Ngoc-Tu; Nguyen, Viet-Anh; Do, Nam-Khanh; Vu, Kim-Duy; Vo, Hoang-Long; Doan, Quoc-Hung (Frontiers in Surgery, 2021)
Background: Little is known about video-assisted thoracoscopic surgery in the Nuss procedure (VATS-NUSS) and its postoperative outcomes in the resource-scare conditions in clinical practice such as Vietnam. Available evidence in the literature was mostly reported from large institutions in developed countries. Hence, this study was conducted to review our initial large single-center experience in the use of the VATS-NUSS for the patients with pectus excavatum (PE) within the five years. Methods: Data from 365 consecutive PE patients between January 2015 and December 2019 who were surgically treated with VATS-NUSS were retrospectively analyzed. Results: Of 365 patients, median age at operation was 15.61 ± 3.73 years (range, 5 to 27 years), most being child and adolescent. Three hundred and nine patients (84.65%) were male. PE was commonly detected at puberty (n = 328, 89.9%). Postoperatively, early complications consisted of pneumothorax (n = 5, 1.37%), pleural bleeding / pleural fluid (n = 2, 0.55%), pleural hematoma (n = 1, 0.27%), pneumonia (n = 1, 0.27%), surgical wound infection (n = 1, 0.27%), incision fluid accumulation (n = 3, 0.82%), metal bar infection (n = 1, 0.27%), atelectasis (n = 3, 0.82%), and fever (n = 8, 2.19%). Late complications included surgical wound infection (n = 2, 0.55%), metal bar deviation (n = 5, 1.37%), metal bar allergy (n = 10, 2.74%), recurrent PE (n = 2, 0.55%), and persistent PE (n = 5, 1.37%). No deaths occurred. In 175 patients (47.95%) experiencing bar removal, mean operative time for bar removal was 34.09 ± 10.61 minutes, and the length of hospitalization following bar removal was 2.4 ± 1.34 days; the most frequent complication was pneumothorax (n = 19, 10.85%); One wound infection and one incision fluid accumulation happened following bar removal. Favourable mid-term to long-term postoperative outcomes were achieved. Conclusions: From the beginning of the Vietnamese surgeons’ experience, VATS-NUSS application obtained favorable outcomes with minimizing the occurrence of serious intra- and postoperative complications. Current rare evidence enables to give a real picture in the application, modification and development of VATS-NUSS in the countries having similar resource-scare conditions.